Women and social movements in Latin America : power from below - Stephen, Lynn (University of Texas Press, 1997)
"This innovative, comparative study explores six cases of women's grassroots activism in Mexico, El Salvador, Brazil, and Chile. Lynn Stephen communicates the ideas, experiences, and perceptions of women who participate in collective action, while she explains the structural conditions and ideological discourses that set the context within which women act and interpret their experiences. She includes revealing interviews with activists, detailed histories of organizations and movements, and a theoretical discussion of gender, collective identity, and feminist anthropology and methods."--Jacket.